Asthma-related sudden death in athletes: a retrospective analysis of the US NCCSIR database (1982–2018). Issue 1 (1st July 2021) - Price, Oliver J.; Kucera, Kristen L.; Price, Hannah M.; Drezner, Jonathan A.; Menzies-Gow, Andrew; Hull, James H.
Asthma is the most common medical condition in athletes, with a reported prevalence of approximately 20% [1]. Over the past two decades, the impact of asthma on athletic performance has been extensively studied [2]; however, research focussing specifically on asthma-related death in athletes is limited to one study, with Becker et al. [3] reporting a series of 61 deaths over a 7-year period (1993–2000), either during or in close proximity with a sporting event. We therefore undertook this study to provide comprehensive insight into the incidence of asthma-related mortality in competitive athletes. Asthma remains a rare but important cause of sudden death in young athletes. Approximately one athlete with asthma died per year, thus highlighting that with appropriate medical management, sports participation for people with asthma is generally safe. https://bit.ly/3r9dE5t